Analisis Peran BAZNAS Kabupaten Deli Serdang Dalam Pembentukan UPZ Mesjid Desa Payageli - Gifari Maulana; Syaddan Dintara Lubis (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2026)
This study aims to analyze the role of BAZNAS Deli Serdang Regency in the establishment of Zakat Collection Unit (UPZ) at the Payageli Village Mosque based on Government Regulation Number 14 of 2014 concerning Zakat Management. In its provisions, the establishment of Zakat Collection Unit (UPZ) at the village level must be approved by BAZNAS. Empirical juridical research with a sociological approach where primary data was obtained through interviews with the Deputy Chairperson of BAZNAS Deli Serdang Regency and mosque administrators in Payageli Village after tracing relevant laws and regulations. The results of the study indicate that BAZNAS Deli Serdang Regency has attempted to conduct socialization and coordination related to the establishment of UPZ at the District level but has not been optimal. Although zakat collection by BKM Payageli Mosque has been beneficial, the legality is not in accordance with the law so that it requires ongoing coordination and guidance from BAZNAS.